Before the dust settles: a Nama Arts and Culture exhibition complex Springbok, Northern Cape - Olivier, Bianca (University of the Free State, 2021)
The acts of preserving and exhibiting ephemeral African arts are important, as it safeguards cultural identities for generations. In order for museums and galleries to preserve art, the idea of the white cube was developed. The white cube, however, faces issues when attempting to capture and display ephemeral arts that are dependent on factors which include time, context, artist and the chosen creative material or medium, to exist. These art forms are usually independent on what galleries and museums offer, including the presence of an audience or viewers. Land art, however, introduces key ideas on exhibiting ephemeral art that mark a permanent cultural presence in the world. The Nama-Khoi ethnic group of Namaqualand are well-known for their artistic capabilities and hand-down rituals, especially the “Rieldans”. These art forms embody an impermanence to its aesthetic, where it’s manifested to the world only for a brief moment at no particular time, and in the natural landscape at no particular place. Due to this, these artistic practices are starting to gather dust as it seldom experience an audience. This research document sets out to investigate architecture as land art form to provide a cultural setting as platform for the recognition and celebration of Nama-Khoi artistic practices. The Nama-Khoi “Rieldans” is investigated as concept generator to facilitate in choreographing the design and experience of a Nama Arts and Culture exhibition complex located in the tourist hub and heart of Namaqualand, Springbok, Northern Cape. The aim of the proposal is to embody the essence of the “Rieldans” in an architectural intervention that is both a destination and interactive building.
Keywords: Dissertation (M.Arch. (Architecture))--University of the Free State, 2021; Ephemerality; Permanency; Embodiment; Land art; White cube; “Rieldans”; Preservation of art